Pengaruh Dewan Komisaris, Komite Audit, Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Corporate Social Responsiblity Disclosure Pada Perusahaan Manufaktur 2016-2020 - Anis Sriwahyuni (Eastasouth Institute, 2023)
Corporate Social Responsibility (CSR) is a form of corporate responsibility towards social and environmental issues, such as improving the welfare of the community and the environment so that the quality of human resources in the area where the company operates increases. The purpose of this study was to determine the effect of the board of commissioners, audit committee, profitability, liquidity and firm size on CSRD. This type of research is quantitative research with an associative approach. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The technique used in taking the sample is purposive sampling with a total sample of 16 companies. The analysis technique used in this study is multiple regression analysis for hypothesis testing and in processing the data using the SPSS 24 program. The results of the study indicate that the variables of the board of commissioners, audit committee, profitability as proxied by ROA and ROE have no effect on the disclosure of corporate social responsibility.